Digital wars : Apple, Google, Microsoft and the battle for the Internet - Arthur, Charles, 1961- (London ; Philadelphia : Kogan Page, 2012)
'Digital Wars' assesses who will be the victor and what the implications are for business, individuals and society. Accessible and comprehensive, it looks at the very different cultures of each business, the iPhone, Android, iPods (mobile music) and the browser and apps battles.
1998 -- Microsoft antitrust -- Search : Google versus Microsoft -- Digital music : Apple versus Microsoft -- Smartphones -- Tablets -- 2011.
Keywords: Internet industry -- United States; Apple Computer, Inc; Google (Firm); Microsoft Corporation